2023
DOI: 10.1021/acsptsci.3c00031
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Antibody Blunts Carfentanil-Induced Respiratory Depression

Abstract: Carfentanil, the most potent of the fentanyl analogues, is at the forefront of synthetic opioid-related deaths, second to fentanyl. Moreover, the administration of the opioid receptor antagonist naloxone has proven inadequate for an increasing number of opioid-related conditions, often requiring higher/additional doses to be effective, as such interest in alternative strategies to combat more potent synthetic opioids has intensified. Increasing drug metabolism would be one strategy to detoxify carfentanil; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Respiratory stimulants with promising results in animal or human studies include nicotinic acetylcholine receptor agonists, ampakines, potassium channel blockers, partial opioid receptor agonists or antagonists, scrubber molecules, and monoclonal antibodies against specific opioids (including antibodies that enhance opioid metabolism). 8,54 Still, none of these strategies is currently sufficiently scrutinized to allow definite conclusions regarding effectiveness and safety. For example, it remains unknown whether these strategies are able to overcome severe respiratory depression (e.g., ventilation less than 40% of baseline, gasping, or apnea) and are able to prevent cardiac arrest.…”
Section: Naloxone Alternatives: Agnostic Respiratory Stimulantsmentioning
confidence: 99%
“…Respiratory stimulants with promising results in animal or human studies include nicotinic acetylcholine receptor agonists, ampakines, potassium channel blockers, partial opioid receptor agonists or antagonists, scrubber molecules, and monoclonal antibodies against specific opioids (including antibodies that enhance opioid metabolism). 8,54 Still, none of these strategies is currently sufficiently scrutinized to allow definite conclusions regarding effectiveness and safety. For example, it remains unknown whether these strategies are able to overcome severe respiratory depression (e.g., ventilation less than 40% of baseline, gasping, or apnea) and are able to prevent cardiac arrest.…”
Section: Naloxone Alternatives: Agnostic Respiratory Stimulantsmentioning
confidence: 99%
“…[ 123 ] Murine, chimeric and humanized antibodies have been developed to capture or catalyze fentanyl and its analogs to counteract opioid toxicity. [ 124 , 125 , 126 ] For instance, a humanized monoclonal antibody, C10‐S66K displayed a high binding capacity to fentanyl and carfentanil (100‐fold more potent than fentanyl). Intraperitoneal injection of 30 mg kg −1 C10‐S66K antibody significantly alleviated respiratory depression caused by carfentanil overdose ( Figure 3 a ).…”
Section: Pk Approaches: Nano‐antidotes Sequestering Anesthetics For D...mentioning
confidence: 99%
“…[123] Murine, chimeric and humanized antibodies have been developed to capture or catalyze fentanyl and its analogs to counteract opioid toxicity. [124][125][126] For instance, a humanized monoclonal antibody, C10-S66K displayed a high binding capacity to Two-way RM ANOVA was employed for statistical analysis; * p > 0.05, # p > 0.001. Reproduced with permission.…”
Section: (Nano)-antidotes With High Affinity Recognizing Unitsmentioning
confidence: 99%
“…The improved scFv, C10-S66K scFv-ABD, with a suitable in vivo t 1/2 was then tested in our respiratory depression mouse model using whole body plethysmography. Carfentanil displays dose-dependent respiratory depressive effects causing a measurable decrease in respiratory minute volume (MV), a product of tidal volume and respiratory rate. , Typically, a 30 μg/kg dose (IP) produces an ∼70% reduction in MV at maximum respiratory depression, 15 min post drug administration. In prior studies, we have demonstrated blockade of carfentanil’s respiratory depressive effects by vaccine elicited serum antibodies as well as passive immunization strategies; , however, a more pertinent model for counteracting drug intoxication as a countermeasure would be to demonstrate reversal of drug-induced respiratory depression post-exposure.…”
mentioning
confidence: 99%